Prefrontal activation in bipolar and unipolar depression patients in the letter fluency tasks and category fluency tasks: a functional near-infrared spectroscopy study - Hui, Juan; Dai, Haiyue; Lu, Qi; Wang, Juan; Cui, Guimei; Mu, Junlin; Zhao, Lin; Gu, Shina; Li, Juan; Zhang, Zhaohui (Frontiers in Psychiatry, 2025)
BackgroundDistinguishing bipolar disorder (BD) from unipolar depression (UD) remains a critical clinical challenge. Improved diagnostic accuracy could enhance therapeutic outcomes for both conditions. This study aims to (1) identify functional near-infrared spectroscopy (fNIRS)-based biomarkers differentiating BD from UD, and (2) compare frontotemporal hemodynamic responses during phonological (LFT) and semantic (CFT) verbal fluency tasks.MethodsWe recruited 100 participants: 33 with UD, 34 with BD, and 33 healthy controls (HC). Cortical oxygenation changes ([oxy-Hb]) were recorded using 52-channel fNIRS during LFT and CFT performance.FindingsThe [oxy-Hb] activation in the UD and BD groups was lower compared to the HC group. Most channels demonstrated the [oxy-Hb] activation is lowest in BD patients, followed by UD patients, and the highest in the HC participants. Compared to CFT, UD and HC patients exhibited more extensive prefrontal cortex activation during LFT. This study found differences in [oxy-Hb] activation in the ventrolateral prefrontal cortex (VLPFC) between BD and UD patients during the CFT period.ConclusionOur findings indicate that the LFT elicits more extensive prefrontal activation, with differential engagement of the VLPFC in BD compared to UD. These results suggest potential neuroimaging biomarkers for distinguishing between UD and BD, while also providing insights into the neural substrates of language processing.